2010
DOI: 10.2147/vhrm.s8175
|View full text |Cite
|
Sign up to set email alerts
|

Aliskiren and valsartan combination therapy for the management of hypertension

Abstract: Combination therapy is necessary for most patients with hypertension, and agents that inhibit the renin-angiotensin-aldosterone system (RAAS) are mainstays in hypertension management, especially for patients at high cardiovascular and renal risk. Single blockade of the RAAS with an angiotensin-converting enzyme (ACE) inhibitor or angiotensin receptor blocker (ARB) confers some cardiorenal protection; however, these agents do not extinguish the RAAS as evidenced by a reactive increase in plasma renin activity (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
18
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 69 publications
0
18
0
Order By: Relevance
“…10 Although pharmacologic manipulation of the reninangiotensin system with ACEIs and ARBs improves outcomes in hypertension and cardiovascular and renal disease, it provides only partial protection from disease progression. 13 Possible mechanisms for the inadequacies include interruption of negative feedback and a compensatory increase in renin and angiotensin I levels, which can overcome ACE inhibition or result in the production of angiotensin II (Ang II) by non-ACE pathways (i.e. ACE escape).…”
Section: Introductionmentioning
confidence: 99%
“…10 Although pharmacologic manipulation of the reninangiotensin system with ACEIs and ARBs improves outcomes in hypertension and cardiovascular and renal disease, it provides only partial protection from disease progression. 13 Possible mechanisms for the inadequacies include interruption of negative feedback and a compensatory increase in renin and angiotensin I levels, which can overcome ACE inhibition or result in the production of angiotensin II (Ang II) by non-ACE pathways (i.e. ACE escape).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, they are not able to completely block RAAS activity because of the reactive rise in renin release induced by the withdrawal of the feedback inhibition exerted by AngII (the so-called short feedback loop), as evidenced by a reactive increase in plasma renin activity (PRA), a well-established cardiovascular risk marker, 18 providing an incomplete cardiorenal protection. 19 The central role of the RAAS in the pathogenesis of diabetic nephropathy is accepted because several studies have shown that ACE-is and ARBs can significantly reduce diabetic nephropathy. [20][21][22][23][24][25] Blockade of the RAAS with ACE-is or ARBs may be delayed; however, this delay does not avoid the progression of diabetic nephropathy towards end-stage renal disease (ESRD).…”
Section: Introductionmentioning
confidence: 99%
“…31 By blocking the first and rate-limiting step in the RAAS, aliskiren reduces PRA by at least 70% and buffers the compensatory increase in PRA observed with ACE-is and ARBs. 19 The combination of a DRI and an ARB or an ACE-i is an effective approach for lowering BP and available data indicate that such combinations favourably affect proteinuria, left ventricular mass index and brain natriuretic peptide levels in patients with albuminuria, LVH and HF. 15,19,24,32 Four different trials evaluated the potential cardiorenal effects of aliskiren on morbidity and mortality.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…3 ALIS has been extensively investigated in randomized controlled trials as monotherapy and in various free and single-pill combinations. [4][5][6][7] However, the drug is less well documented with regard to its effectiveness and safety under clinical practice conditions. [8][9][10] Particular interest has been given to the combination of ALIS with an ACE inhibitor or ARB, ie, dual RAS blockade, as ALIS was expected to block the compensatory rise of plasma renin activity (PRA) induced by RAS inhibitors acting downwards in the cascade.…”
mentioning
confidence: 99%